NAFLD: Reporting Histologic Findings in Clinical Practice. Issue 5 (29th April 2021) - Brunt, Elizabeth M.; Kleiner, David E.; Carpenter, Danielle H.; Rinella, Mary; Harrison, Stephen A.; Loomba, Rohit; Younossi, Zobair; Neuschwander‐Tetri, Brent A.; Sanyal, Arun J.; ,
Abstract : The role of liver biopsy in NASH has evolved along with the increased recognition of the significance of this disease, and the unmet medical need it presents. Drug development and clinical trials are rapidly growing, as are noninvasive tests for markers of steatosis, inflammation, injury, and fibrosis. Liver biopsy evaluation remains necessary for both drug development and clinical trials as the most specific means of diagnosis and patient identification for appropriate intervention. This White Paper, sponsored by the American Association for the Study of Liver Disease NASH Task Force, is a focused review of liver biopsy evaluation in fatty liver disease in subjects with presumed NAFLD for practicing clinical hepatologists and pathologists. The goal is to provide succinct and specific means for reporting the histopathologic elements of NASH, distinguishing NASH from nonalcoholic fatty liver without steatohepatitis, and from alcohol‐associated steatohepatitis when possible. The discussion includes the special situations of NASH in advanced fibrosis or cirrhosis, and in the pediatric population. Finally, there is discussion of semiquantitative methods of evaluation of lesions of "disease activity" and fibrosis. Tables are presented for scoring and a suggested model for final reporting. Figures are presented to highlight the histopathologic elements of NASH.